PERFORMANCE EVALUATION IN STANDARD TCP AND UDP USING NS3 SIMULATOR - Monday Simon; Alexander Ntino; Christopher Akarinwan (Galaxy International Interdisciplinary Research Journal, 2023)
User Datagram Protocol (UDP) and Transmission Control Protocol (TCP) are a transportation layer routing protocols which are considered of the main protocols of the internet protocol suite. The attribute of these routing protocols with different network metrics and scenarios is still not very clear. Therefore, this research discusses a comparison of the performance of both TCP and UDP to determine which of these protocols is better in terms of latency and throughput. Network Simulator (NS3) is utilized to analyze and evaluate the performance for both TCP and UDP protocols varying in the packet size and the bandwidth. In this paper, we use two situations, in the first situation the bandwidth has been adjusted with fixed packet size and in the second situation the packet size has been adjusted with fixed bandwidth to actually validate the performance of these protocols. These protocols were examined in terms latency and throughput. The results have referred that TCP outperformed UDP in terms of the latency while UDP outperformed TCP in terms of throughput